A Comparative Analysis of the Public and Private Water Supply and Sanitation Service Providers’ Work in Brazil - Fernando Antonio Perrone Pinheiro; José Roberto Ferreira Savoia; Claudio Felisoni de Angelo (BBR: Brazilian Business Review)
This paper aims to evaluate the performance of the private management of water supply and sanitation services in Brazil. We can verify therefore, whether this management model has presented superior performance compared to the model of public management. The analysis was based on various economic-financial and operational indices related to water supply and sewage collection and treatment between 2000 and 2010. The results indicate that private companies outperform public entities in several aspects, like productivity, investment, return and access to these services, pointing out the concessions and public-private partnerships are feasible ways to reach political targets of universalization of Water Supply and basic Sanitation.